Silvopastoral restoration to enhance ecosystem services and increase farmers' income - Louhaichi, Mounir; Gamoun, Mouldi; Hamdeni, Imtinene; Hassan, Sawsan; Slim, Slim; Jamel, Kailene; Ates, Serkan (Curran Associates, 2024)
Silvopastoral systems (SPS) are deemed as agroecological solutions that hold great potential to reduce pressure on already degraded forest and rangeland resources while synergistically enhancing livestock productivity and improve farmers’ livelihoods. Despite the vital role of SPS in improving the livelihoods of rural people, they are subject to human and climate drivers that can result in reduced productivity. This study aims to develop a sustainable SPS in Central Tunisia to alleviate the anthropogenic effects of climate change through establishing a SPS, in which shrubs/trees are combined with persistent pasture species and beekeeping activity. Native legume species such as sulla (Hedysarum coronarium), shrubs species such as tree medick (Medicago arborea) and tree species such as carob (Ceratonia siliqua) were used to improve soil quality, enhance carbon sequestration, income diversification and biodiversity conservation. Results indicated a higher biomass production from sulla planted areas (5.3 t DM/ha) than control pastures (1.2 t DM/ha). Similarly, a substantial improvement in total carbon (0.79% vs. 0.16%) in topsoil (0-20 cm), organic matter (1.37% vs. 0.28%) and total nitrogen (1.39% vs. 0.78%) were recorded through incorporating sulla in pastures. With 15 hives per ha in sulla plots combined with substantial reduction in the cost of livestock feeding, a noticeable increase was reflected in the income of farmers in the region. Therefore, diversification of the SPS using forage legume-pollinator is strongly recommended for strengthening SPS and improving livelihood of the Mediterranean silvopastoral communities